Investigation of polymer drug conjugates for pancreatic cancer - Anane-Adjei, Akosua Bema (2020)
Pancreatic ductal adenocarcinoma (PDAC) is one of the most fatal forms of cancer with a 10-year survival rate of <1 %. Although considerable advancement has been made in understanding the biology of the disease, most patients presenting with locally advanced or metastatic disease have an extremely poor prognosis. Gemcitabine (GEM), a nucleoside analogue of cytidine is the first-line treatment for patients diagnosed with locally advanced or metastatic disease. However, approx. 90 % of the intravenously administered dose of GEM undergoes rapid deamination in the bloodstream by cytidine deaminase (CDA), affecting the drug’s therapeutic efficiency. Due to this, large doses are needed to achieve significant therapeutic efficacy leading to increased adverse effects.